Effects of salidroside on atherosclerosis: potential contribution of gut microbiota - Fei, Si-Fan; Hou, Can; Jia, Fang (Frontiers in Pharmacology, 2024)
Much research describes gut microbiota in atherosclerotic cardiovascular diseases (ASCVD) for that the composition of the intestinal microbiome or its metabolites can directly participate in the development of endothelial dysfunction, atherosclerosis and its adverse complications. Salidroside, a natural phenylpropane glycoside, exhibits promising biological activity against the progression of ASCVD.Recent studies suggested that the gut microbiota played a crucial role in mediating the diverse beneficial effects of salidroside on health. Here, we describe the protective effects of salidroside against the progression of atherosclerosis. Salidroside regulates mucosal barrier through its ability to suppress NF-κB and p38 MAPK signaling pathways, modulate the NF-κB/MAPK/JAK-STAT3 signaling pathways and increase the expression of antimicrobial peptides HD-5 and HD-6. c. Salidroside can reduce TMAO production through reducing the abundance of Firmicutes and Proteobacteria. d. Salidroside can improve the expression of SCFAs, through increasing the abundance of some special bacteria. e. Salidroside can reduce LPS-induced inflammation, which is associated with the inhibition of the ROS-mediated PI3K/AKT/mTOR signaling pathway, the down-regulation of exosome miR-199a-5p, and the attenuation of the Notch-Hes signaling pathway. f. Salidroside can inhibit NLRP3-associated gut-coronary axis, including TLR4/MyD88/NF-κB/NLRP3 signaling pathway, AMPK/NF-κB/NLRP3 signaling pathway, and P2X7/NF-κB/NLRP3 signaling pathway.endothelial function and alleviates atherosclerosis by activating a mitochondria-related AMPK/PI3K/Akt/eNOS pathway.